Formulas for stress, strain, and structural matrices - Pilkey, Walter D. (John Wiley & Sons, 2005)
This is a reference source for strength of material formulas for the analysis and design of structural members and mechanical elements. Allows efficient static, stability and dynamic analyses of beams, bars, plates and shells with very general mechanical or thermal loading. The range of solutions includes arbitrary geometries and loadings.